Partnering for Grand Challenges: A Review of Organizational Design Considerations in Public–Private Collaborations - George, Gerard; Fewer, Thomas J.; Lazzarini, Sergio; McGahan, Anita M.; Puranam, Phanish (Journal of Management, 2024)
We conduct a theory-guided review of the literatures on public–private partnerships and grand challenges (GCs). We adopt an organization design approach to review and identify constructs in public–private collaborations (PPCs) that address societal challenges. Our review identifies the complexities of organizing to tackle GCs, highlights the plurality of organizational forms in PPCs, and explores organizational design considerations in these partnerships. Given the elevated role of private actors in these collaborations, our review provides a new understanding of how they can shape a private-public interface that is robust to the scale and scope of global problems. This leads to a rich research agenda on when, why, and how public and private collaborations matter, and their implications for addressing societal challenges.